2014
DOI: 10.1172/jci70156
|View full text |Cite
|
Sign up to set email alerts
|

WNT5A enhances resistance of melanoma cells to targeted BRAF inhibitors

Abstract: About half of all melanomas harbor a mutation that results in a constitutively active BRAF kinase mutant (BRAF V600E/K ) that can be selectively inhibited by targeted BRAF inhibitors (BRAFis). While patients treated with BRAFis initially exhibit measurable clinical improvement, the majority of patients eventually develop drug resistance and relapse. Here, we observed marked elevation of WNT5A in a subset of tumors from patients exhibiting disease progression on BRAFi therapy. WNT5A transcript and protein were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 70 publications
8
155
0
Order By: Relevance
“…Indeed, high expression of Wnt5a, a marker of the invasive phenotype, was found to induce resistance to BRAF inhibitors in patients (14). In vitro-acquired data show the same trendthe invasive phenotype can be linked to both intrinsic and acquired resistance to BRAF or MEK inhibitors (13,15).…”
Section: Reactivation Of the Mapk Pathway Confers Resistance To Targementioning
confidence: 79%
“…Indeed, high expression of Wnt5a, a marker of the invasive phenotype, was found to induce resistance to BRAF inhibitors in patients (14). In vitro-acquired data show the same trendthe invasive phenotype can be linked to both intrinsic and acquired resistance to BRAF or MEK inhibitors (13,15).…”
Section: Reactivation Of the Mapk Pathway Confers Resistance To Targementioning
confidence: 79%
“…We also evaluated our CTL PLX4720 and BMI PLX4720 populations for the expression of DE genes that are up-regulated by BMI1 and known to be key determinants for BRAFi resistance in melanoma, such as EGFR, PDGFR, and Wnt5a Anastas et al 2014;Sabbatino et al 2014;Sun et al 2014). We found that Wnt5a was further up-regulated in all of the BMI PLX4720 populations, compared with vehicle-treated BMI1 controls, and was also specifically induced in the CTL PLX4720 line that had up-regulated its endogenous BMI1 (Fig.…”
Section: Bmi1 Confers Resistance To Braf Inhibitor Treatmentmentioning
confidence: 99%
“…In this context WNT5A was increased in BRAF inhibitor-resistant cell lines and in patient tumors, leading to a promotion of melanoma growth. (66,67) Another study dealing with changes in energy metabolism found WNT5A to increase the aggressive behavior of melanoma cells beyond the enhancement of aerobic glycolysis. (68) In contrast, downregulation of WNT5A showed inhibitory effects on melanoma cell invasion.…”
Section: Melanomamentioning
confidence: 99%
“…Yes (137)(138)(139) Yes (140) Breast cancer (89) ; melanoma (66) ; ovarian cancer (141) 38,40) ). Inhibition of FZD5 resulted in inhibited proliferation and migration (2 (75) ).…”
Section: Rykmentioning
confidence: 99%
See 1 more Smart Citation